Analysis of the use of repulsors to improve generalization ability in genetic programming : an application to symbolic regression problems - Canelhas, Jorge Miguel Silvestre (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management